Investigation into learning strategies and delexical verb use by Thai EFL learners - Rachata Kittigosin,; Supakorn Phoocharoensil, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
Research into delexical structures is not common in Thailand and is in fact a neglected area of investigation despite the fact that knowledge of collocations can improve language competence. This study investigated the learning strategies that caused deviant delexical-verb use by Thai EFL learners. The study was undertaken with two groups of Thai EFL learners of differing English proficiencies who completed a 20-item gap-filling translation test and participated in an interview. The results revealed that learners relied on three major learning strategies - native language transfer, synonymy, and overgeneralisation that could lead to uncommon and deviant use of English delexical structures by learners. It was also discovered that both high and low proficiency learners were most familiar with the delexical verb take. The study also revealed that teachers of English should consider the significant role of these strategies when preparing English collocations and lessons on delexical verbs.